Neuromodulation possibilities in neurogenic lower urinary tract dysfunction - G. Yu. Yarin; E. I. Kreydin; R. V. Salyukov; E. V. Kasatonova; S. V. Astrakov; A. V. Bershadsky; I. A. Vilgelmi; A. I. Shevela (Вестник урологии)
Introduction. Neuromodulation has proven itself in the treatment of patients suffering from idiopathic overactive bladder and non-obstructive urinary retention, who are resistant to conservative therapy. The possible use of the method in the population of patients with neurogenic lower urinary tract dysfunction (NLUTD) is of undoubted clinical interest.Objective. To analyze the current possibilities and features of neuromodulation in a cohort of patients with NLUTD.Materials and methods. Original research materials published in the PubMed, eLibrary, SciVerse (ScienceDirect), Scopus, Medline, EMBASE databases, websites of professional associations without restrictions on the date of publication were used. Sixty sources were selected for citation, with preference given to systematic reviews, meta-analyses and RCTs .Results. In relation to NLUTD, transcranial and peripheral magnetic stimulation, intravesical electrical stimulation, tibial, pudendal electrical stimulation, and stimulation of the dorsal pudendal nerve, as well as sacral and epidural methods of neurostimulation are considered.Conclusion. The current literature optimistically presents the experience of using neuromodulation in the NLUTD patient population with the largest evidence base for invasive sacral and tibial stimulation. The studies are based on heterogeneous populations, limited by small sample sizes with insufficient descriptive part of the degree and severity of neurological diseases, and it should be considered when forming guidelines. However, the lack of other suitable therapies and promising initial results indicate the importance of further efforts to improve the applied methods of neuromodulation. Further studies are needed with larger sample sizes, better classification of diseases, and controlled study design